2019
DOI: 10.1088/1367-2630/ab1309
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced viscoelasticity in cytocompatible hydrogel substrates

Abstract: Human mesenchymal stem cells (hMSCs) sense and respond to the bulk elastic and viscoelastic properties of their microenvironment, as well as the spatial distribution of these mechanical signals.Hydrogel substrates with photo-controlled mechanical properties can allow one to probe the cellular response to localized variations in substrate viscoelasticity. Here, we report on a cytocompatible hydrogel culture system that allows photo-induced changes in viscoelasticity via an additionfragmentation chain transfer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 44 publications
(62 reference statements)
0
25
0
Order By: Relevance
“…Besides physically crosslinked hydrogels, the hydrogels containing dynamic covalent chemistries, such as thioester, [ 47,175–177 ] allyl sulfide, [ 178 ] disulfide, [ 158 ] hydrazone, [ 48,179,180 ] boronate, [ 49,50,181 ] oxime, [ 182–184 ] Schiff base, [ 185–187 ] and Diel–Alder [ 188–190 ] that create covalent adaptable networks can also possess viscoelasticity. Thioester‐containing hydrogels were fabricated via thiol‐ene click chemistry to yield adaptable networks ( Figure A).…”
Section: Tunable Viscoelastic Hydrogels Formed Through Varying Crosslinking Strategiesmentioning
confidence: 99%
“…Besides physically crosslinked hydrogels, the hydrogels containing dynamic covalent chemistries, such as thioester, [ 47,175–177 ] allyl sulfide, [ 178 ] disulfide, [ 158 ] hydrazone, [ 48,179,180 ] boronate, [ 49,50,181 ] oxime, [ 182–184 ] Schiff base, [ 185–187 ] and Diel–Alder [ 188–190 ] that create covalent adaptable networks can also possess viscoelasticity. Thioester‐containing hydrogels were fabricated via thiol‐ene click chemistry to yield adaptable networks ( Figure A).…”
Section: Tunable Viscoelastic Hydrogels Formed Through Varying Crosslinking Strategiesmentioning
confidence: 99%
“…As an example, allyl sulfide moieties in hydrogels can act as on‐off switches to trigger the sequential exchange of biochemical cues employing the chain transfer reaction of a thiyl radical. [ 198 ] Other examples have demonstrated the possibility to generate hydrogels with tunable viscoelastic [ 199 ] and cell release [ 200 ] properties on‐demand. The chain exchange offered by the allyl sulfide functional group is limited to the consumption of the activating radical spices.…”
Section: Fabrication Of Patterns By Precise Chemical Designmentioning
confidence: 99%
“…(d) Reproduced with permission under the terms of the CC‐BY‐3.0 license. [ 99 ] Copyright 2019, the Authors. Published by IOP Publishing.…”
Section: Applications Of Biomaterials To Study Fibrosismentioning
confidence: 99%
“…[ 98 ] Similarly, PEG hydrogels with phototunable viscoelasticity showed that the introduction of local areas of viscoelasticity induces rapid retraction of MSC protrusions, suggesting that subcellular‐sized areas of viscoelasticity may determine cell phenotype (Figure 4). [ 99 ] The effects of tissue viscoelasticity, unlike stiffness, are not straightforward and it is likely that the specific ECM factors that contribute to tissue viscoelasticity and ECM storage modulus determine cellular responses to viscoelasticity. [ 100 ] Additionally, further characterization of viscoelastic hydrogels need to be carried out and clearly described as some materials display viscoplastic behavior, [ 65 ] while others do not have plastic behavior within the cell force‐relevant regime.…”
Section: Applications Of Biomaterials To Study Fibrosismentioning
confidence: 99%